Effects of supplementation of calcium salts of polyunsaturated fatty acids on serum concentrations of progesterone and insulin of pregnant dairy cows - Moriel, Philipe [UNESP] (2014)
Forty-five non-lactating, pregnant Holstein animals (18 heifers and 27 multiparous cows; BW = 561±114 kg; BCS = 2.9±0.3; days pregnant = 110±56 d) were stratified by initial BW and BCS, and randomly assigned to receive daily (as-fed basis) 0.50 kg of ground corn plus 0.22 kg of kaolin (CON), calcium salts of saturated fatty acids (SFA) or polyunsaturated fatty acids (PF) for 14 d. Blood samples were collected on days 0, 7 and 14, immediately prior to (0 h) and 3, 6, 9 and 12 h after feeding, to determine the serum concentrations of P4 and insulin. No treatment effects were detected for serum concentrations of P4 (5.52, 6.13 and 5.63±0.41 ng/mL for CON, SFA and PF, respectively). No treatment effects were detected for serum concentrations of insulin (11.5, 10.5 and 10.1±1.43 μIU/mL for CON, SFA and PF, respectively). Heifers had greater serum concentrations of P4 than multiparous cows (6.35 vs. 5.16±0.42 ng/mL), but lower serum concentrations of insulin (7.0 vs. 14.4±1.49 μIU/mL). Feeding 0.22 kg of calcium salts of polyunsaturated fatty acids is not sufficient to increase the serum concentrations of P4 and insulin of non-lactating, pregnant dairy cows. © 2014 Sociedade Brasileira de Zootecnia.